Developments in tick vaccines–An update - T, MUFEEDA; A, SHAHARDAR R; A, WANI Z; H, BULBUL K; M, ALLAIE I; A, INSHA; H, KHAN A (The Indian Journal of Animal Sciences, 2023)
Ticks are the obligate haematophagous and economically important ectoparasites parasitizing various domestic and wild animals, especially amphibians, reptiles, birds and mammals. They are second to mosquitoes in terms of being competent and versatile vectors of many bacterial, viral, protozoan and rickettsial diseases. They are responsible for causing direct and indirect losses to livestock industry. Current control methods are primarily based on use of acaricides. Due to the development of acaricide resistance, environment contamination and residues in meat and milk, control of ticks through immunization appears to be most feasible, cost-effective and environment friendly method. Identification of protective tick antigen is the main limiting step in vaccine development. Tick antigen should have critical function in tick, so that if the function is disrupted, it would lead to death or reduce the fecundity at the levels that will impact the tick population. Various protective, exposed and concealed candidate antigens have been identified and characterized by adopting different strategies like immune-mapping, expression library immunization (EST), RNA interference and bioinformatics. In this review, an attempt has been made to present a comprehensive account on vaccine development in ticks.